2013
DOI: 10.1159/000353215
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mononuclear Cell Transplantation Increases Metalloproteinase-9 and 13 and Decreases Tissue Inhibitors of Metalloproteinase-1 and 2 Expression in the Liver of Cholestatic Rats

Abstract: Liver fibrosis results from chronic injury followed by activation of macrophages and fibrogenic cells like myofibroblasts and activated hepatic stellate cells. These fibrogenic cells express α-smooth muscle actin (α-SMA) and produce excessive extracellular matrix (ECM), with disorganization and loss of function of hepatic parenchyma. It is known that increased levels of metalloproteinases (MMPs) in liver fibrosis are associated with reduction of the pathologic ECM and fibrosis resolution. Recently, it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…; Nunes de Carvalho et al . ). MMPs do not respond uniformly during pathology and some MMPs promote fibrogenesis, whereas others contribute to fibrolysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Nunes de Carvalho et al . ). MMPs do not respond uniformly during pathology and some MMPs promote fibrogenesis, whereas others contribute to fibrolysis.…”
Section: Discussionmentioning
confidence: 97%
“…Another means by which NASH related fibrosis may be regulated is via alterations in extracellular matrix remodelling proteins because of their ability to regulate collagen turnover. Circulating MMPs are increased in NASH (D'Amico et al 2010), whereas models of liver fibrosis have increased the hepatic expression of MMPs (Wanninger et al 2011;Nunes de Carvalho et al 2013). MMPs do not respond uniformly during pathology and some MMPs promote fibrogenesis, whereas others contribute to fibrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between high collagen levels and decreased α-SMA positive myofibroblasts may therefore also be explained if α-SMA myofibroblasts have decreased already, while collagen has not been cleared yet. Since matrix metalloproteinases (MMPs) are normally mostly produced by macrophages ( 23 , 24 ), and macrophages were also decreased by rapamycin treatment in our study, it is possible that the deposited collagen was not cleared due to a lack of MMPs. However, an increased deposition of collagen by other cell types than myofibroblasts cannot be excluded based on our findings.…”
Section: Discussionmentioning
confidence: 82%
“…Runx2 and Osterix are considered to be the most important transcription factors that regulate the stereotype and differ- entiation of osteoblasts, which are the key site for a variety of hormones that regulate the osteoblast differentiation and bone formation of local and external regulatory factors (24). Scholars have confirmed that high-concentration hormones are able to inhibit the expression and activity of osteoblast phenotype markers Runx2 and Osterix by investigating in-vitro cell culture and the molecular and genetic level (25). In present study, pretreatment with Sal B significantly increased Runx2 and Col I protein expression levels in steroid-induced osteonecrosis rats.…”
Section: Discussionmentioning
confidence: 99%